2014
DOI: 10.5152/solunum.2014.25993
|View full text |Cite
|
Sign up to set email alerts
|

Serum Magnesium Concentration in Children with Asthma

Abstract: Objective: Asthma is the most common chronic disease of childhood, and magnesium is one of the most frequently found minerals in human body and it is used in the treatment of asthma. Although there are studies on magnesium levels in adult patients with asthma, there is yet no data on the levels of magnesium in children. The present study compared the levels of serum magnesium between the children with asthma and healthy children. Methods:Children aged between 5 and 17 years with mild-moderate persistent asthma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(20 reference statements)
1
2
0
Order By: Relevance
“…This is also in concordance to the indings of the studies conducted by Siebes KD et al, Mohammed NS et al, and Ahmed AA et al [7][8][9]. Nevin et al, also concluded that the mean serum magnesium levels are lower like the current study [10]. However the study conducted by karkish KS et al, found no such co relation [11].…”
Section: Discussionsupporting
confidence: 92%
“…This is also in concordance to the indings of the studies conducted by Siebes KD et al, Mohammed NS et al, and Ahmed AA et al [7][8][9]. Nevin et al, also concluded that the mean serum magnesium levels are lower like the current study [10]. However the study conducted by karkish KS et al, found no such co relation [11].…”
Section: Discussionsupporting
confidence: 92%
“…Stable asthma was defined as absence of asthma exacerbations for four weeks preceding presentation. 7 The inclusion criteria for the control group were: (a) Children aged 6 -16 years, without asthma and other respiratory diseases such as pneumonia, pulmonary tuberculosis (b) Children not on any medication that can affect magnesium level e.g diuretic therapy, calcium blockers. (c) Children without chronic illnesses such as renal diseases, malignancy, sickle cell disease, determined through historical information and physical examination.…”
Section: Methodsmentioning
confidence: 99%
“…A significant share of total body Mg is intracellular, estimation of which is difficult. [ 20 ] Serum Mg levels may not correlate with intracellular levels. Furthermore, normal controls were not included.…”
Section: Discussionmentioning
confidence: 99%